The production of 7-methyljuglone, plumbagin and quercetin in wild and cultivated Drosera rotundifolia and Drosera intermedia - B. Baranyai; C. Bäcker; C. Reich; U. Lindequist (Mires and Peat, 2016)
The recent establishment of Sphagnum farming areas has created large artificial habitats where Drosera grows under semi-natural conditions. Here we test the suitability, for pharmaceutical purposes, of two Drosera species collected from such areas. We measured the concentration of the biologically active compounds 7-methyljuglone, plumbagin and quercetin in Drosera rotundifolia and D. intermedia. All three compounds were found in pharmacologically suitable concentrations with 7-methlyjuglone characteristic for D. rotundifolia and plumbagin for D. intermedia. The concentrations required for pharmacological purposes were achieved within one year, but higher concentrations occurred in older plants and plants in flower. Concentrations did not differ between plants collected in the morning and in the afternoon. Drosera plants cultivated under semi-natural conditions are suitable as sources of raw materials for industrial pharmacological applications.